STRATEGIES FOR ENHANCING THE COMPETITIVENESS OF SERVICES IN HIGHER EDUCATION INSTITUTIONS: INTERNATIONAL EXPERIENCE AND LOCAL PRACTICE - Haytmetova Nasiba Narimanovna, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: This study explores strategies for enhancing the competitiveness of services in higher education institutions (HEIs), emphasizing both international experience and local practices. The research examines global trends in higher education, including quality improvement, innovative service delivery, and student-centered approaches. It also analyzes the challenges faced by local universities in implementing competitive strategies and proposes recommendations to strengthen their market position. The findings highlight the importance of integrating international best practices with local context to achieve sustainable development in higher education services.